Effects of Melatonin and Vitamin C on Cigarette-Induced Structural Changes in the Trachea - Ozan, Enver; Çolakoğlu, Neriman; Sönmez, Mehmet Fatih; Ozan, Sema; Yılmaz, Seval; Taşdemir, Bülent; Ozan, Gonca (Fırat University, 2005)
Objectives: This study was undertaken to investigate smoke-induced structural and biochemical changes and protective effects of co-administred of melatonin and vitamin C in rat trachea. Materials and Methods: Twenty-four Wistar female rats were used. Animals were divided into four groups. The first group of rats used as control. The second group of rats were inhalated cigarette. Cigarette inhalated third and fourth group of rats recieved melatonin and vitamin C respectively. At the end of the study trachea tissues and blood samples were taken under the anesthesia. Tissues were prepared and examined by light microscopy. And biochemically, malondialdehyde and glutathione levels and catalase activities were determined. Results: Microscopically, blood and desquamation of epithelial cells in the tracheal lumen, activated granular cells and apoptotic cells in the epithelial layer and activated serous gland in the submucosal layer were detected in the group II. In the group III and IV melatonin and vitamin C relatively protected the trachea tissue against smoke intoxication. Biochemical examination showed malondialdehyde levels in the group II higher than group I, melatonin and vitamin C injection to group III and IV caused to decrease of malondialdehyde. Glutathione levels and catalase activity in the group II were less than group I. Melatonin and vitamin C injection did not change the decrease of the glutathione levels and catalase activities in group III and IV. Conclusion: As a result, cigarette inhalation increased lipid peroxidation and antioxidant system and caused structural changes. However, melatonin and vitamin C administration obtained relative protection against smoke.©2005, Fırat Üniversitesi, Tıp Fakültesi

Amaç: Sigara toksikasyonunun trakea dokusunda oluşturduğu yapısal ve biyokimyasal değişiklikler üzerine C vitamini ve melatoninin koruyucu etkilerinin belirlenmesi amaçlandı. Gereç ve Yöntem: Bu çalışmada 24 adet Wistar cinsi ergin dişi sıçan kullanıldı. Sıçanlar 4 gruba ayrıldı. Birinci grup sıçanlar kontrol olarak kullanıldı, ikinci grup sıçanlara sigara inhale ettirildi. Sigara soluyan üçüncü ve dördüncü grup sıçanlara ise hergün sırasıyla melatonin ve C vitamini enjekte edildi. Deney sonunda sıçanlardan eter anestezisi altında trakea dokuları ve kan örnekleri alındı. Dokuların bir kısmı rutin histolojik prosedürlerden geçirilerek ışık mikroskobunda incelendi. Biyokimyasal olarak, malondialdehit (MDA) ve glutatyon düzeyleri ile katalaz aktiviteleri belirlendi. Bulgular: Işık mikroskobik incelemelerde ikinci grupdaki sıçanların trakea lümeninde kan ve epitelyal hücre döküntüleri, epitel tabakasında apoptozise giden hücrelere ve aktive olmuş granüllü hücrelere rastlandı. Submukozadaki seröz bezlerde aktivasyon tespit edildi. Üçüncü ve dördüncü gruplarda melatonin ve C vitamininin trakea dokusunu sigara toksikasyonuna karşı kısmen koruduğu gözlendi. Yapılan biyokimyasal incelemelerde, sigara inhale eden grupta MDA düzeylerinin kontrol grubuna göre önemli ölçüde arttığı, C vitamini ve melatonin enjeksiyonunun ise artan MDA düzeyini azalttığı saptandı. Katalaz aktivitesi ve glutatyon düzeyi ise sigara inhale eden grupta kontrol grubuna göre düşüş gösterirken, C vitamini ve melatoninin bu düşüşü önemli derecede etkilemediği gözlendi. Sonuç: Sigara inhalasyonunun, lipid peroksidasyonunu ve antioksidan sistemi artırdığı, trakea dokusunda yer yer yapısal değişiklikler oluşturduğu tespit edildi. C vitamini ve melatoninin ise sigara toksikasyonuna karşı kısmen koruma sağladığı gözlendi. ©2005, Fırat Üniversitesi, Tıp Fakültesi
Sigara İnhalasyonunun Trakea'da Oluşturduğu Yapısal Değişiklikler Üzerine Melatonin ve C Vitamininin Etkileri